2018
DOI: 10.1080/0284186x.2017.1423179
|View full text |Cite
|
Sign up to set email alerts
|

First report of proton beam therapy for breast angiosarcoma from the prospective PCG registry

Abstract: View related articles View Crossmark data manifestation is thought to be related to dosing interval and the cumulative number of chemotherapy cycles [1,2]. Even though nail and skin toxicity are not life threatening, effective management to ameliorate the symptoms is a necessity to allow patients to continue their chemotherapy regimen. In some cases, patients may require dose adjustment, as was the case in a series of three patients with PATEO syndrome described by Rodriguez-Lomba et al. [3] Despite developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…All patients in our series had clinical and radiologic evidence of extensive disease, most achieved a pathologic complete response, and none developed a local recurrence (5 of 6 patients had follow-up exceeding 16 months). This series adds to a case report published on proton therapy for breast angiosarcoma in which patients were treated postoperatively with conventional fractionation to a median dose of 60 Gy [ 62 ]. Similar to our series, favorable dosimetry was achieved with proton therapy.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in our series had clinical and radiologic evidence of extensive disease, most achieved a pathologic complete response, and none developed a local recurrence (5 of 6 patients had follow-up exceeding 16 months). This series adds to a case report published on proton therapy for breast angiosarcoma in which patients were treated postoperatively with conventional fractionation to a median dose of 60 Gy [ 62 ]. Similar to our series, favorable dosimetry was achieved with proton therapy.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 However, a randomized phase II trial showed that paclitaxel administered once per week with bevacizumab showed no superior bene t over paclitaxel without bevacizumab in patients with advanced angiosarcoma. In several cases, CTLA-4 inhibitors, PD-1 directed therapy, proton beam therapy and photodynamic therapy showed therapeutic bene ts, [40][41][42][43] and these might be potential future options. There is a compelling need to explore novel therapeutic strategies for breast angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether radiation therapy can be conducted remains a question, as SBA is induced by previous radiation therapy. Additionally, reports have emerged on proton beam radiotherapy for BA postoperative treatment [ 35 ]. Hyperfractionated radiotherapy demonstrates benefits for local control and survival rates [ 3 ].…”
Section: Postoperative Adjuvant Therapymentioning
confidence: 99%